THE IMPACT OF BIBLE-BASED MULTISENSORY INSTRUCTION ON INDONESIAN TODDLERS - Maria Priscilla Viledy; Agustinar Centhya (12th International Scholars Conference 2025, 2026)
This study investigates the impact of multisensory Bible-based instruction on Indonesian toddlers aged 1–3. Conducted over 12 weeks at an Adventist Christian early childhood Sabbath school in Bandung, West Java. The study incorporated thematic storytelling, songs, and sensory play rooted in the "Alive in Jesus" curriculum which is based on multisensory teaching method. Data were collected through structured classroom observations and parental questionnaires. The findings revealed consistent engagement, enhanced vocabulary recognition, notable character development, and spiritual connection. Triangulation indicated alignment between observed behaviors and parental perception of cognitive and behavioral growth. These results support the feasibility and potential of multisensory instruction in early bilingual education.